Esophageal disease - Pech, Oliver (Endoscopy, 2013)
During the 2013 Digestive Disease Week (DDW) (May 18 – 21, Orlando, Fla) many exciting and important endoscopy-related studies on esophageal disease were presented. Most studies were on diagnosis and endoscopic treatment of Barrett’s esophagus and related neoplasia. However, also other topics such as eosinophilic esophagitis, peroral endoscopic myotomy (POEM) in achalasia patients, Zenker’s myotomy, and endoscopic treatment of squamous cell cancer had several relevant scientific contributions.The following review discusses my personal subjective selection of 18 important endoscopy abstracts from this year’s DDW.